Botulinum toxin: Non cosmetic and off-label dermatological uses - Ali S. Al-Ghamdi; Noah Alghanemy; Hanan Joharji; Dhafer Al-Qahtani; Hasan Alghamdi (Wolters Kluwer Medknow Publications, 2015)
Botulinum toxin (BT-A) is a neurotoxin which is produced by the Gram-positive anaerobic bacterium Clostridium botulinum. The efficacy of Botulinum toxin in treating hyperhidrosis and the glabellar lines is well known and FDA approved. Because BT-A inhibits the release of acetylcholine and many other neurotransmitters such as norepinephrine and substance P at the level of nerve ending, this toxin has been used to treat a lot of dermatological disorders which are thought to be triggered by these neurotransmitters. In this article we are discussing the medical off-label uses of BT-A in dermatology.